Structural Asymmetry in two Thallium-based Alloys: Tl-Mg and Tl-Na - Panthi, Narayan; Bhandari, Indra Bahadur; Koirala, Ishwar (Journal of Institute of Science and Technology, 2024)
Different modelled equations are used to analyze the variation of the thermodynamic, microscopic and surface characteristics between the Tl-Mg and Tl-Na liquid alloys at 1000 K by considering TlNa2 and TlMg2 complexes. The Thermodynamic properties are studied under Quasi-Chemical Approximation and the agreement between theoretical and experimental results of thermodynamic properties about their melting temperatures verifies the validity of model. The transport and surface properties of the alloys are studied by Kaptay and Butler models respectively. From the theoretical observations, it is shown that the Tl-Mg alloy is more interacting than that of the Tl-Na alloy and exhibits an ordering nature below 0.3 concentration of Tl, but above this concentration Tl-Na alloy shows more ordering tendency. The Tl-Mg has a higher viscosity than the Tl-Na alloy within whole concentration of Tl. On the basis of surface properties, Na segregates on the surface within entire concentration of Tl in Tl-Na alloy whereas Mg segregates on the surface below 0.35 concentration of Tl in Tl-Mg alloy.